Pathophysiology of Hypertensive Heart Disease: Beyond Left Ventricular Hypertrophy - Nwabuo, Chike C.; Vasan, Ramachandran S. (Current hypertension reports, 2020)
Purpose of Review Given that the life expectancy and the burden of hypertension are projected to increase over the next decade, hypertensive heart disease (HHD) may be expected to play an even more central role in the pathophysiology of cardiovascular disease (CVD). A broader understanding of the features and underlying mechanisms that constitute HHD therefore is of paramount importance. Recent Findings HHD is a condition that arises as a result of elevated blood pressure and constitutes a key underlying mechanism for cardiovascular morbidity and mortality. Historically, studies investigating HHD have primarily focused on left ventricular (LV) hypertrophy (LVH), but it is increasingly apparent that HHD encompasses a range of target-organ damage beyond LVH, including other cardiovascular structural and functional adaptations that may occur separately or concomitantly. HHD is characterized by micro- and macroscopic myocardial alterations, structural phenotypic adaptations, and functional changes that include cardiac fibrosis, and the remodeling of the atria and ventricles and the arterial system. In this review, we summarize the structural and functional alterations in the cardiac and vascular system that constitute HHD and underscore their underlying pathophysiology.